2011
DOI: 10.5751/ace-00470-060202
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Conservation Trade-offs: Demographic Models Provide Critical Context to Empirical Studies

Abstract: . 2011. Measuring conservation trade-offs: demographic models provide critical context to empirical studies. Avian Conservation and Ecology 6(2): 2. http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…There are at least two ways in which the presence of the predator may increase the risk of abandonment. First, if a predator removes one adult, the energetic demands of continued incubation and subsequent brood-rearing may be too great for the remaining parent (Calvert and Taylor 2011), which could lead to nest abandonment. Abandonment by the remaining bird following the mortality of its mate has been observed in a banded population of Piping Plovers in the Great Lakes region (Roche et al 2010), although it remains unclear that the disappearance of a mate caused abandonment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are at least two ways in which the presence of the predator may increase the risk of abandonment. First, if a predator removes one adult, the energetic demands of continued incubation and subsequent brood-rearing may be too great for the remaining parent (Calvert and Taylor 2011), which could lead to nest abandonment. Abandonment by the remaining bird following the mortality of its mate has been observed in a banded population of Piping Plovers in the Great Lakes region (Roche et al 2010), although it remains unclear that the disappearance of a mate caused abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…As with other species, nest exclosures increase plover hatching success, but are also associated with higher rates of adult mortality and nest abandonment (Neuman et al 2004). This is cause for concern as increased adult mortality, in particular, can have significant impacts on population growth (Calvert and Taylor 2011;Watts et al 2012) and therefore poses a greater risk to species persistence than the loss of eggs (Isaksson et al 2007). Thus, determining if exclosures affect the behaviour of adult plovers or their predators in ways that increase mortality and nest abandonment is required to determine if the continued use of this management tool is warranted.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…, Roche et al . ) and thus has different demographic consequences than other nest failure types and may offset the benefits of increased hatching rates at exclosed nests (Calvert & Taylor ). In such a context, modelling nest survival alone as a function of exclosure use is not sufficient to predict population‐level consequences; more generally, if a covariate has opposing effects on different types of nest failure, then its importance can only be revealed through a multi‐fate study (Etterson et al .…”
mentioning
confidence: 99%
“…Few models have been developed to estimate separately the rates of failure due to different causes, although understanding the factors that lead to different types of nest failure can be of management interest. For example, abandonment at Piping Plover Charadrius melodus nests with wire exclosures (Melvin et al 1992) has been shown to be indicative of adult mortality due to predators targeting incubating adults as they leave exclosures (Murphy et al 2003, Barber et al 2010, Roche et al 2010) and thus has different demographic consequences than other nest failure types and may offset the benefits of increased hatching rates at exclosed nests (Calvert & Taylor 2011). In such a context, modelling nest survival alone as a function of exclosure use is not sufficient to predict population-level consequences; more generally, if a covariate has opposing effects on different types of nest failure, then its importance can only be revealed through a multi-fate study (Etterson et al 2007a).…”
mentioning
confidence: 99%